Peningkatan Kecakapan Ilmiah (Scientific Abilities) Mahasiswa Melalui Model Eksperimen Penerapan (Application Experiments) - Basid, Abdul; Abtokhi, Ahmad (UPEJ Unnes Physics Education Journal, 2021)
Each course must be designed to help students acquire valuable skills that will be applied in the workplace. Various efforts were made to improve students' scientific abilities, including developing learning models in the laboratory. Research has been carried out using a research and development design approach to improve students' scientific abilities through an model spplications experiments. There are seven experimental topics that 20 students have to do in this model. Of the seven topics, there are six scientific sub-abilities that students must develop in this model. From the results of the written student lab reports from the 1st to the 7th experiment, it showed that the students' scientific abilities increased and stabilized after the 5th experiment or at the 5th week. Of all the developed sub- abilities, the average percentage of scientific proficiency achievement scores reached 60% in almost all sub- abilities after the 4th experiment. This shows that the student's scientific abilities reaches 60% after the student conducts the experiment in the fourth week. Indeed, there are several sub- abilities whose achievements have reached 60% in the 3rd experiment, including scientific skills in designing experiments to solve problems and skills in identifying assumptions.